Demokrasi dan Hukum dalam Bingkai Wawasan Kebangsaan - Christina Maya Indah (PAX HUMANA, 2015)
Democracy need law supremacy that guarantee of equality, respect for human right, justice, protection, and respect for civil and political right in the frame of unity in diversity perspective. Nation perspective intent to be a culture in democracy and law as the institution of multicultural society. Democracy refuses destructive harmonization in the perspective of nation. Monoculturalism politic, domination, hegemony, radicalism, stereotype, discrimination, majority and minority dichotomy with support by law of sectarian are an anomaly of democracy in multiculturalization condition. The respect of dignity human being in law only can be built as long as no relation sectarianism in group ideology with politic af?iliation, and politics of recognition of multiculturalism according Pancasila as the source of source of law. In the frame of nation perspective, democracy will be characterized of law which agree with peace building. Revitalization of nation perspective can be done through dissemination of peace education in order to reach solidarity and tolerancy as the public awareness. Keywords: Democracy, Law, Nation, Perspective